WESTERN BALKANS DIGITAL SUMMIT: TOWARDS EFFECTIVE DIGITALIZATION PROCESS GOVERNANCE IN THE REGION - Dunjić, Ivana (National interest, 2024)
The digital revolution is leading to structural changes in the system of global relations and shaping a new and different environment in which diplomacy unfolds. Technological innovations have opened up new possibilities that point to one of the fundamental roles of diplomacy in the digital age - “the creation of networks, embracing a range of state and non-state actors focusing on the management of issues that demand resources over which no single participant possesses a monopoly” (Hocking 2006). The changed constellation of global relations promised to present an opportunity to initiate positive economic, political, and social changes in the world. Nevertheless, the digitalization process is characterized by unevenness because it is influenced by broader economic and socio-political factors. That explains why not all regions possess the potential for digital transformation. The global challenge of the digital divide is a reality in many parts of the world. The same applies in the Western Balkans. However, the Western Balkans are trying to reduce the digital gap through regional cooperation in digitalization. This multilateral process was initiated in 2017 through the Berlin process. This led to the establishment of a Digital Summit framework for consultations, negotiations, and deliberation on challenges and perspectives of digitalization and digital transformation. From 2018 to 2023, the Western Balkans Digital Summit was held six times in the capitals of the Western Balkan Six. Within this research, Digital Summit is thoroughly analyzed as a specific case of “multistakeholder summitry” (West 2006) reflecting the crucial role of diplomacy as an activity of the creation of networks that Hocking pointed out. The research question is whether the Western Balkans Digital Summit, as a new dimension of regional cooperation, contributed to a more effective digitization process of regional governance. The empirical research showed positive results. Although the digital gap is still a reality, not only in the Western Balkans but also in all parts of the world, it is smaller compared to the period before the start of the Digital Summit. This is shown by the abolition of roaming charges in the region and the initiation of price reductions in comparison with equivalent services in the European Union. The process of digitalization is accelerated, not only as a result of the Digital Summit process but also a combination of various circumstances. Nevertheless, the regional approach of the multistakeholder summit is a significant contribution to global digitalization governance. The Western Balkans Digital Summit contributed to more effective regional digitalization governance. Consequently, it represents an example of good practice of regional cooperation in global issues, as well as one that preserves continuity and highlights the importance of digital transformation, including each region into global flows.